Expansion glue as well as preparation method and application thereof

By using materials such as styrene butadiene rubber, nitrile rubber and PVC paste resin in the expansion glue, combined with talc as filler, an expanded glue with high initial adhesion and high foaming rate was prepared, which solved the problem of poor bonding and sealing effect of existing expanded glue between automotive sheet metal parts, and achieved excellent shock absorption and sealing performance.

CN119736034APending Publication Date: 2025-04-01HANGZHOU ZHIJIANG SILICONE CHEM +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510017387.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing expansion glue has poor sealing effect between thinner sheet metal parts inside and outside the automobile and the larger gap between sheet metal parts, which cannot fully meet the application requirements in automobile manufacturing.

Method used

Styrene butadiene rubber and nitrile rubber are used, PVC paste resin and talc powder are added as fillers, and coupling agent and crosslinking agent are combined to prepare expanded rubber with high initial adhesion, low curing strength and high foaming rate.

Benefits of technology

It realizes excellent shock absorption and sealing performance in the inner and outer sheet metal, engine cover, suitcase cover and other parts of the car door. It is suitable for connecting parts that require shock absorption or fill gaps, and has good aging resistance and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005230298390000021
    Figure BDA0005230298390000021
  • Figure BDA0005230298390000071
    Figure BDA0005230298390000071
  • Figure BDA0005230298390000082
    Figure BDA0005230298390000082
Patent Text Reader

Abstract

The invention relates to expansion glue as well as a preparation method and application thereof. The expansion glue is prepared from the following raw materials: butadiene styrene rubber, nitrile rubber, PVC paste resin, filler, a coupling agent, a cross-linking agent and a plasticizer. Styrene-butadiene rubber and nitrile rubber are matched and kneaded to obtain butylbenzene / butyronitrile mixed rubber with better corrosion resistance and elastic property, PVC paste resin is supplemented, so that the expansion rubber is easier to foam and has excellent chemical stability, and a coupling agent is further added to promote all the components to generate a synergistic effect, so that the expansion rubber is more environment-friendly. Meanwhile, the damage form of an adhesive interface of the expansion glue is improved, so that the finally obtained expansion glue has excellent initial adhesiveness, high foaming rate and low shear strength, and is more suitable for shock absorption between thinner sheet metal parts of a vehicle body and sealing of larger gaps between the sheet metal parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, and in particular to an expansion adhesive and a preparation method and application thereof. Background Art

[0002] Low-strength high-foaming expansion glue is a paste product with synthetic rubber as the main component. It is used for filling between the inner and outer panels of automobiles. It is a heat-cured product that is cured by baking and has the main purpose of shock absorption, sealing and bonding. It is used in the welding process of various outer and inner panels, reinforced plates, etc. of automobiles, and can also be used on engine hoods, doors, trunk lids and other parts. When using ordinary shock-absorbing sealants for bonding inner and outer panels, it cannot be completely filled due to the shape changes of the spraying. There will still be gaps after baking and curing, and the purpose of sealing has not been achieved; some expansion glues have too strong adhesion, which causes some thinner sheet metals to deform or dent after baking, curing and foaming, affecting the appearance of the whole vehicle; in addition, some of them have insufficient initial adhesion to oil-surface steel plates, which will also cause the expansion glue to fall off and detach during the pre-treatment and electrophoresis process; some of them have insufficient foaming ratio after baking and curing, and the gap cannot be filled, and the interface peeling phenomenon will occur, resulting in noise, rust and other problems.

[0003] In order to prevent the vibration propagation between the outer panel and the reinforcing ribs, currently, polymer material products such as expansion glue and expansion tape are used between the outer panel and the reinforcing ribs of the automobile for vibration reduction. Such materials are cured through an electrophoresis process to form a highly elastic rubber that connects the outer panel and the reinforcing ribs together. By applying such products, the effects of vibration prevention, resonance control, and damping are achieved, thereby avoiding or eliminating low-frequency vibrations of the vehicle and improving the NVH performance of the vehicle. CN107345011A discloses a high-foaming expansion glue, which increases the contact area with the substrate after curing and expansion through the high foaming rate of the expansion glue to achieve a better seismic isolation effect. Although it can reach a high foaming rate of 120-160%, the existing expansion glue products have poor effects on the bonding between thinner sheet metal parts inside and outside the door, as well as the sealing effect of larger gaps between sheet metal parts, and cannot fully meet the application requirements.

[0004] Therefore, developing an expansion adhesive with high initial adhesion, low strength after curing, high foaming rate and excellent aging resistance has become a technical problem that urgently needs to be solved in this field. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides an expansion adhesive and a preparation method and application thereof. The expansion adhesive has a high initial viscosity before curing, and is in an elastomeric state after baking, curing and foaming. It has excellent shock absorption and sealing properties and is suitable for use in inner and outer sheet metal of automobile doors, engine hoods, trunk lids, roof beams and other connection parts that require shock absorption or gap filling.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides an expansion adhesive, wherein the raw materials for preparing the expansion adhesive include the following components: styrene-butadiene rubber, nitrile-butadiene rubber, PVC paste resin, filler, coupling agent, cross-linking agent and plasticizer.

[0008] Preferably, the raw materials for preparing the expansion glue include the following components in parts by weight:

[0009]

[0010] Among them, the styrene-butadiene rubber can be 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts or 14 parts, etc.

[0011] Among them, the nitrile rubber can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts, etc.

[0012] Among them, the PVC paste resin can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts or 11 parts, etc.

[0013] Among them, the filler can be 17 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts or 45 parts, etc.

[0014] The coupling agent may be 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts or 0.8 parts, etc.

[0015] The cross-linking agent may be 0.5 parts, 0.7 parts, 1 part, 1.2 parts or 1.5 parts, etc.

[0016] Among them, the plasticizer can be 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts or 30 parts, etc.

[0017] The invention adds PVC paste resin into the styrene-butadiene rubber / nitrile-butadiene rubber system, so that the rubber system has excellent paste-forming property and dispersing property, and the prepared expansion rubber has excellent foaming property and aging resistance.

[0018] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0019] Preferably, the raw materials for preparing the expansion adhesive further include any one of a foaming agent, a foaming aid, a flame retardant, a water absorbent or an anti-aging agent, or a combination of at least two thereof.

[0020] Preferably, the raw materials for preparing the expansion adhesive contain 0.8 to 2 parts of foaming agent, for example, 0.8 parts, 1 part, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts or 2 parts.

[0021] Preferably, the raw materials for preparing the expansion adhesive contain 1 to 2.2 parts of a foaming aid, for example, 1 part, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2 parts or 2.2 parts.

[0022] Preferably, the raw materials for preparing the expansion adhesive contain 5 to 10 parts of flame retardant, for example, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts.

[0023] Preferably, the raw materials for preparing the expansion adhesive contain 2 to 4 parts of water absorbent, for example, 2 parts, 2.5 parts, 3 parts, 3.5 parts or 4 parts.

[0024] Preferably, the raw materials for preparing the expansion glue contain 0.2 to 0.8 parts of anti-aging agent, for example, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts or 0.8 parts.

[0025] Preferably, the filler includes any one of nano-active calcium carbonate, heavy calcium carbonate or talcum powder, or a combination of at least two of them.

[0026] Preferably, the filler comprises nano-activated calcium carbonate and talc.

[0027] Preferably, the mass ratio of nano-activated calcium carbonate to talc in the filler is 1:(1-2), for example, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9 or 1:2, etc.

[0028] The preferred technical solution of the present invention uses talcum powder to replace a part of calcium carbonate. The talcum powder can play a role of skeleton as a filler, which improves the stability of the colloid while reducing the manufacturing cost, and further has a certain reinforcing effect on the colloid. In addition, the present invention uses talcum powder as the main filler, which avoids the dissolution and shedding of the expansion glue when the filler is heavy calcium carbonate or nano-active calcium carbonate during the operation of the pre-treatment liquid.

[0029] Preferably, the crosslinking agent is a peroxide crosslinking agent.

[0030] Preferably, the peroxide cross-linking agent includes any one of dicumyl peroxide, benzoyl peroxide, di-tert-butyl peroxide or dicumyl hydroperoxide, or a combination of at least two thereof.

[0031] Preferably, the coupling agent comprises a silane coupling agent.

[0032] Preferably, the plasticizer includes any one of dioctyl phthalate, dimethyl phthalate, diethyl phthalate, diisononyl phthalate, dihexyl phthalate or di-n-butyl phthalate, or a combination of at least two thereof, and more preferably diisononyl phthalate.

[0033] Preferably, the blowing agent comprises an azo compound and / or a sulfonylhydrazide compound.

[0034] Preferably, the foaming aid comprises zinc oxide.

[0035] Preferably, the flame retardant includes any one of aluminum oxide, aluminum hydroxide, and magnesium hydroxide, or a combination of at least two of them.

[0036] Preferably, the water absorbing agent comprises calcium oxide.

[0037] Preferably, the anti-aging agent includes an antioxidant.

[0038] In a second embodiment, the present invention provides a method for preparing the expansion adhesive as described in the first aspect, characterized in that the preparation method comprises: mixing styrene-butadiene rubber, nitrile-butadiene rubber, PVC paste resin, filler, coupling agent, cross-linking agent, optional foaming agent, optional foaming aid, optional flame retardant, optional water absorbent, optional anti-aging agent and plasticizer to obtain the expansion adhesive.

[0039] Preferably, the mixing is carried out in a kneader.

[0040] Preferably, the mixing temperature is below 80°C, for example, it may be 50°C, 55°C, 60°C, 65°C, 70°C or 75°C.

[0041] Preferably, the mixing time is 3-5 h, for example, 3 h, 3.5 h, 4 h, 4.5 h or 5 h.

[0042] In a third embodiment, the present invention provides a use of the expansion adhesive as described in the first aspect in shock absorption between body sheet metal parts and filling gaps between body sheet metal parts.

[0043] Preferably, the sheet metal part includes any one of an oily steel plate, an aluminum plate or a galvanized plate.

[0044] Compared with the prior art, the present invention has at least the following beneficial effects:

[0045] (1) The expansion adhesive provided by the present invention is prepared by combining styrene-butadiene rubber and nitrile rubber to obtain a styrene-butadiene rubber / nitrile rubber mixed rubber with better corrosion resistance and elasticity, and is supplemented with PVC paste resin, so that the expansion adhesive is easier to foam and has excellent chemical stability. A proper amount of coupling agent is further added to promote the synergistic effect of each component and improve the bond interface failure shape of the expansion adhesive. The expansion adhesive finally obtained has excellent initial adhesion, high foaming rate and low bonding strength, and is more suitable for body sheet metal shock absorption and bonding between thin sheet metal parts, as well as sealing of large gaps between sheet metal parts.

[0046] (2) The preferred technical solution of the present invention uses talcum powder to replace a part of calcium carbonate. Talc powder can play a role as a skeleton as a filler, which reduces the manufacturing cost and improves the stability of the colloid, and further has a certain reinforcement effect on the colloid. In addition, the present invention uses talcum powder as the main filler, which avoids the dissolution and shedding of the expansion glue during the operation of the pre-treatment liquid, etc. due to the filler being heavy calcium carbonate or nano-activated calcium carbonate.

[0047] (3) Specifically, the expansion adhesive provided by the present invention has good extrudability and excellent foaming rate, the pressure flow viscosity is 127.08-178.59 g / min; the foaming rate is 84.12-196.34%; the storage stability is 17.6-19.4%, the shear strength at room temperature is 0.05-0.34 MPa, the shear strength after wet heat aging is 0.05-0.33 MPa, and it has excellent resistance to wet heat aging. DETAILED DESCRIPTION

[0048] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0049] In the following specific implementation of the present invention, the specific information of the materials used is as follows:

[0050] 1. Styrene butadiene rubber, 1502, purchased from Sinopec;

[0051] 2. Nitrile rubber, P83, purchased from Shengbang Materials;

[0052] 3. PVC paste resin, LP-170, purchased from LG Chemical;

[0053] 4. Butadiene rubber, BR9000, purchased from Sinopec;

[0054] 5. Coupling agent, KH560, purchased from Chenguang, etc.;

[0055] 6. Cross-linking agent, 4,4-di-tert-butyl peroxide, 17-40B, purchased from Shanghai Moyan Chemical;

[0056] 7. Water absorbent, calcium oxide, RSF052, purchased from Kexiang New Materials;

[0057] 8. Plasticizer, dioctyl phthalate DINP, purchased from Shanghai Huiluo Trading;

[0058] 9. Blowing agent, azodicarbonamide OBSH, purchased from LANXESS;

[0059] 10. Foaming aid, zinc oxide, ZnO Xinji, Shanghai Meilian Chemical;

[0060] 11. Anti-aging agent, antioxidant 1010, BASF;

[0061] 12. Flame retardant, aluminum hydroxide, 505D, Xusen flame retardant.

[0062] Example 1

[0063] A swelling adhesive, wherein the raw materials for preparing the swelling adhesive include the following components: 12 parts of styrene-butadiene rubber, 8 parts of nitrile rubber, 9 parts of PVC paste resin, 20 parts of talcum powder, 13.5 parts of nano-active calcium carbonate, 0.5 parts of coupling agent, 0.8 parts of cross-linking agent, 1.2 parts of foaming agent, 1.5 parts of foaming aid, 7 parts of flame retardant, 2.6 parts of water absorbent, 0.3 parts of anti-aging agent and 24 parts of plasticizer.

[0064] The preparation method of the swelling adhesive comprises the following steps: mixing the above-mentioned raw materials according to the formula in a kneader at 70° C. for 3 hours to obtain the swelling adhesive.

[0065] Examples 2-15, Comparative Examples 1-4

[0066] Examples 2-15 and Comparative Examples 1-4 respectively provide an expansion adhesive and a preparation method thereof, which differ from Example 1 only in that the types and / or amounts of components are different, as shown in Table 1-2 (the amounts of each component in Table 1-2 are all parts by weight), wherein “--” represents that the component is not added; the preparation method of the expansion adhesive is the same as that of Example 1.

[0067] Table 1

[0068]

[0069]

[0070] Table 2

[0071]

[0072] Test method:

[0073] (1) Pressurized flow viscosity: under standard conditions, the pressurized flow viscometer is used for measurement, the pressure is set to 0.5 MPa, the diameter of the extrusion tube is 3 mm, the extrusion time is 1 min, the weight of the extruded expansion rubber is weighed, and the ratio of the weight of the obtained expansion rubber to the extrusion time is the pressurized flow viscosity of the expansion rubber.

[0074] (2) Foaming rate: Pour about 1 / 2 of pure water into a 500mL measuring cup, place the measuring cup on an open electronic balance to reset it, and suspend clean stainless steel of 50mm×50mm×1mm in water with a 0.5mm thin copper wire to weigh it, and obtain the weight M1. Wipe the steel plate dry, reset the electronic scale, and then use a glue gun to apply the expansion glue on the steel plate. The length of the glue is about 20mm and the diameter is about 10mm. Suspend the stainless steel and the glue in water together to weigh the mass M2. Bake the sample in an oven at 170℃ for 20min, then take it out and cool it for 4 hours, and suspend the sample in water to weigh the mass M3.

[0075] Test results: Foaming rate E (%) = [(M3-M1) / (M2-M1)] × 100%.

[0076] (3) Storage stability: The sample after the rotational viscosity has been measured is placed at a constant temperature of 40°C for 168 hours, then taken out and placed under standard conditions for 4 hours. The rotational viscosity is then re-measured and the viscosity change rate is calculated.

[0077] (4) Sample preparation: Shear module sample: Prepare an oil test piece substrate with a size of 100×25×0.7 mm, apply the sample glue on the test piece, the coating area is 25×25 mm, and the thickness of the glue layer is 2-3 mm. Then overlap and overlap another same test piece with it, scrape off the excess sample glue, clamp it from both sides with two clamps, put it in a high temperature 170℃ oven for 20 min, take it out, place it at room temperature for 4 h, and then conduct the following tests;

[0078] Shear strength: After the shear module is cured, place it in an environment of (23±2)℃ for 4 hours and then test its strength;

[0079] Resistance to moisture and heat aging: After the shear module is cured, it is placed in an aging test box at 70°C and 95% RH for 240 hours, and then the shear strength is tested after being placed at (23±2)°C for 24 hours.

[0080] Test Results

[0081] The expansion adhesives provided in Examples 1-15 and Comparative Examples 1-5 were tested according to the above test method. The test results are shown in Table 3:

[0082] Table 3

[0083]

[0084] The test results show that:

[0085] (1) The expanded adhesives obtained in Examples 1-15 all have good extrudability and excellent foaming rate, with a pressure flow viscosity of 127.08 to 178.59 g / min; a foaming rate of 84.12 to 196.34%; a storage stability of 17.6 to 19.4%, a shear strength of 0.05 to 0.34 MPa at room temperature, and a shear strength of 0.05 to 0.33 MPa after wet heat aging, and have excellent resistance to wet heat aging.

[0086] (2) It can be seen from Example 1 and Examples 7-10 that when the amount of foaming agent added is 1.2 parts, the obtained expansion glue has the best comprehensive effect. When the foaming agent is reduced to 1 part, the foaming effect of the expansion glue is greatly reduced, but the aging resistance effect is relatively excellent. When the content of the foaming agent in the foaming glue is further increased, although its foaming rate shows an upward trend, its shear strength and aging resistance deteriorate with the increase of the foaming agent content.

[0087] (3) It can be seen from Example 1 and Examples 11-12 that when the swelling adhesive contains only talcum powder or active nano-calcium carbonate, the shear performance of the obtained swelling adhesive is poor.

[0088] (4) It can be seen from Example 1 and Comparative Examples 1-3 that the expanded rubber obtained by combining styrene-butadiene rubber and nitrile rubber in the present invention cannot have both excellent foaming rate and low shear strength compared with only styrene-butadiene rubber, only nitrile rubber or butadiene rubber, and the storage stability of the expanded rubber made of only butadiene rubber is poor.

[0089] (5) It can be seen from Example 1 and Comparative Examples 4-5 that the present invention improves the foaming effect of the expansion adhesive by adding PVC paste resin and silane coupling agent to the expansion adhesive.

[0090] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A swelling adhesive, characterized in that: The raw materials for preparing the expansion rubber include the following components: styrene-butadiene rubber, nitrile-butadiene rubber, PVC paste resin, filler, coupling agent, cross-linking agent and plasticizer.

2. The expansion adhesive according to claim 1, characterized in that: The raw materials for preparing the expansion glue include the following components in parts by weight:

3. The expansion adhesive according to claim 1 or 2, characterized in that: The raw materials for preparing the expansion adhesive also include any one or a combination of at least two of a foaming agent, a foaming aid, a flame retardant, a water absorbent or an anti-aging agent; Preferably, the raw materials for preparing the expansion glue contain 0.8 to 2 parts of a foaming agent; Preferably, the raw materials for preparing the expansion adhesive contain 1 to 2.2 parts of a foaming aid; Preferably, the raw materials for preparing the expansion adhesive contain 5 to 10 parts of flame retardant; Preferably, the raw materials for preparing the expansion glue contain 2 to 4 parts of a water absorbent; Preferably, the raw materials for preparing the expansion adhesive contain 0.2 to 0.8 parts of an anti-aging agent.

4. The expansion adhesive according to any one of claims 1 to 3, characterized in that: The filler includes any one of nano-active calcium carbonate, heavy calcium carbonate or talcum powder, or a combination of at least two thereof; Preferably, the filler comprises nano-active calcium carbonate and talc; Preferably, the mass ratio of talc powder to nano-activated calcium carbonate in the filler is (1-2):

1.

5. The expansion adhesive according to any one of claims 1 to 4, characterized in that: The cross-linking agent is a peroxide cross-linking agent; Preferably, the peroxide cross-linking agent includes any one of dicumyl peroxide, benzoyl peroxide, di-tert-butyl peroxide or dicumyl hydroperoxide, or a combination of at least two thereof.

6. The expansion adhesive according to any one of claims 1 to 5, characterized in that: The coupling agent includes a silane coupling agent; Preferably, the plasticizer includes any one of dioctyl phthalate, dimethyl phthalate, diethyl phthalate, diisononyl phthalate, dihexyl phthalate or di-n-butyl phthalate, or a combination of at least two thereof, and more preferably diisononyl phthalate.

7. The expansion adhesive according to any one of claims 1 to 6, characterized in that: The foaming agent includes an azo compound and / or a sulfonyl hydrazide compound; Preferably, the foaming aid comprises zinc oxide; Preferably, the flame retardant includes any one of aluminum oxide, aluminum hydroxide, and magnesium hydroxide, or a combination of at least two thereof; Preferably, the water absorbing agent comprises calcium oxide; Preferably, the anti-aging agent includes an antioxidant.

8. A method for preparing the swelling adhesive according to any one of claims 1 to 7, characterized in that: The preparation method comprises: mixing styrene-butadiene rubber, nitrile-butadiene rubber, PVC paste resin, filler, coupling agent, cross-linking agent, optional foaming agent, optional foaming aid, optional flame retardant, optional water absorbent, optional anti-aging agent and plasticizer to obtain the expansion rubber; Preferably, the mixing is carried out in a kneader; Preferably, the mixing temperature is below 80°C; Preferably, the mixing time is 3-5 hours.

9. Use of the expansion adhesive as claimed in any one of claims 1 to 7 in shock absorption between body sheet metal parts and gap filling between body sheet metal parts.

10. The use according to claim 9, characterized in that: The sheet metal part includes any one of an oily steel plate, an aluminum plate or a galvanized plate.

Citation Information

Patent Citations

  • High-foaming swelling glue

    CN107345011A

  • Expanding damping adhesive with good oil surface adhesive performance and preparation method thereof

    CN102516900A

  • Thermosetting foamable primer and preparation method thereof

    CN105038432A

  • Preformed automobile-damping expandable rubber belt with good oil surface construction and preparation method therefor

    CN105086856A

  • High-strength low-hardness damping rubber and preparation method thereof

    CN105175816A